The Life Cycle Cost Study Comparison Of Air Conditioning System At Q Building Petra Christian University Surabaya - Devina Kartika Santoso; Jimmy Priatman; Christina Eviutami Mediastika (Dimensi Utama Teknik Sipil, 2020)
Global warming has been increasing since last 5th years. This problem emerged because of the development of highrise building these days. In a building, air conditioning system has the largest percentage of building’s energy consumption, 55-65% of total building’s energy consumption. An efficient and economic air-conditioning system is needed to save energy and operational cost as much as possible. Life cycle cost analysis is conducted to evaluate the air conditioning system by comparing some alternatives system. The datas are retrieved from building management and some supplier, also mechanical and electrical contractors. This research is conducted by calculating the investment cost (C), operational cost (O), maintenance and replacement cost (R), and salvage value (S). Before calculating life cycle cost, all cost is converted with annual worth method. Life cycle cost evaluation is capable to save operational cost up to 34%.